Error correction of digital signal processing devices using non-positional modular codes - Kaplun, D. I.; Klionskiy, D. M.; Bogaevskiy, D. V.; Gulvanskiy, V. V.; Veligosha, A. V.; Kalmykov, I. A. (Automatic control and computer sciences, 2017)
The paper discusses an algorithm for correcting code errors of the residue number system using a positional characteristic. Application of parallel-pipeline computations of this positional characteristic allows us to reduce hardware costs by 7.2% for processing 2-byte data represented in a residue number system code. The main properties of codes allow us to provide the required fault-tolerance for multi-rate DSP devices. The results provided in the paper can be applied to hydroacoustic monitoring tasks.